The influence of temperature on the moisture potential in sod-podzolic soil in the autumn and winter periods of the year - Nikolay Muromtsev; Yury Mazhayskiy; Nikolay Semenov; Kirill Anisimov; Viktor Vityazev; Olga Chernikova (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2020)
The formation features of the potential and temperature dynamics at different levels of soil profile are revealed. The influence of soil temperature in the range of its high positive values on the dynamics of soil moisture potential is established. All lowering of the moisture potential occurs due to an increase in the moisture content. The increase in its content occurs due to precipitation and by pulling moisture from the underlying layers. In winter and in periods with negative temperatures, the moisture content is effected by diffusion of vaporous moisture, and in thawed soil, in liquid form.